HILANGNYA HAK ANAK: STUDI KASUS JAMAAH AHMADIYAH INDONESIA - Teja, Mohammad (Jurnal Aspirasi, 2011)
Sectarian conflict has increased in recent years. The physical and psychological harm is experienced by those who become the victim of violent conflict, especially the children. Government’s handling of the Ahmadiyah conflict seems slow. The process of postconflict rehabilitation of Ahmadiyah children who suffered in various regions, such as by providing facilities for the suffered family felt so less. It gives the impression that the victims get no proper attention from centre and local government. The method used in this paper is literature study, in which the data obtained is from books, articles, newspapers and websites. Government as policy makers has the power to provide protection to citizens who are in conflict situations. A positive process of dialogue must be done between central vs local governments, communities vs governments, and also communities vs communities, so that potential conflict can be anticipated, and therefore the problem can be solved immediately.